Morphological parameters of lobular in situ neoplasia in stereotactic 11‐gauge vacuum‐assisted needle core biopsy do not predict the presence of malignancy on subsequent surgical excision. Issue 1 (20th May 2013) - Bianchi, Simonetta; Bendinelli, Benedetta; Castellano, Isabella; Piubello, Quirino; Renne, Giuseppe; Cattani, Maria Grazia; Stefano, Domenica Di; Carrillo, Giovanna; Laurino, Licia; Bersiga, Alessandra; Giardina, Carmela; Dante, Stefania; et al.
<x xml:space="preserve">Abstract</x> Aims The management of lobular in situ neoplasia (LN) when diagnosed on core biopsy remains a controversial issue. The present study aimed to investigate the association between morphological parameters of LN on vacuum‐assisted needle core biopsy (VANCB) and the presence of malignancy (ductal carcinoma in situ, pleomorphic lobular carcinoma in situ, or invasive carcinoma) at surgical excision (SE). Methods and results The study included 14 pathology departments in Italy. Available slides from 859 cases of VANCB reporting an original diagnosis of flat epithelial atypia, atypical ductal hyperplasia or LN, all with subsequent surgical excision, were reviewed. Overall, 286 cases of LN, pure or associated with other lesions, were identified, and a malignant outcome was reported at excision for 51 cases (17.8%). Among the 149 cases of pure LN, an increased risk of malignancy emerged in women in mammographic categories R4–R5 as compared with those in categories R2–R3 (OR 2.46; P = 0.048). In the series, a statistically significant decreased malignancy risk emerged among cases without determinant microcalcifications (P = 0.04). Conclusions Our results suggest that the diagnosis of pure LN on VANCB warrants follow‐up excision, because clinicopathological parameters do not allow the prediction of which cases will present carcinoma at surgical excision.